SNOMED-Based Knowledge Representation - Rothwell, D. J. (Methods of Information in Medicine, 1995)
A standardized vocabulary and a standardized representation for this vocabulary are necessary prerequisites for the development of a computer-based patient record. A standard conceptual scheme or data structure for this vocabulary must be in place to define clinical events and to share data. SNOMED International is a detailed, fine grained, semantically typed and comprehensive computer processable vocabulary encompassing both human and veterinary medicine. Each term is placed in a standardized data structure that shows the term relationship within its own and other related taxonomic hierarchies. SNOMED International is a standardized vocabulary and data structure suitable for use in the computer-based patient record.
Keywords: SNOMEDlnternational; Standardized Vocabulary; Standardized Data Structure; Computer-based Patient Record